Christ the Representative : Toward a Representational Christology - Bernhardt, Reinhold (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2025)
This book explores how the person and salvific significance of Jesus Christ can be understood within today's secular and religiously plural world. Rather than adopting an exclusivist approach, it presents Christology in a manner that steers clear of both rigid absolutism and reductive relativism. At its core lies a thought-provoking question: how might Christology be interpreted not in opposition to, but in dialogue with, other religious traditions? Engaging with biblical sources, often-overlooked strands of theological heritage, and contemporary theological discourse, the book offers a fresh perspective on the concept of 'incarnation.' It reinterprets it as 'representation,' moving beyond the traditional doctrine of Christ's two natures towards a more dynamic understanding of two fundamental relationships-Jesus' relationship with God and his relationship with humanity. This work was originally published in German as Jesus Christus - Repräsentant Gottes by Theologischer Verlag Zürich (TVZ) in 2021. This English edition has been translated from the original and adapted to the context of Anglo-American theology and religious studies.